The Use of Queuing Theory Improved the Service of a Restaurant - Payal Goswami, G. V. V. Jagannadha Rao, Aloke Verma (Mathematical Statistician and Engineering Applications, 2023)
Queuing theory is the mathematical study of waiting lines, sometimes known as queues. Queue lengths and waiting times can be anticipated using a model developed in queuing theory. A key difficulty that almost every well-known restaurant faces is losing customers due to a long wait in line. This highlights the importance of a numerical model in assisting restaurant management in better understanding the issue. This study attempts to demonstrate that queueing theory meets the model when evaluated in a real-world context. For example, data from the Raipur restaurant "Minerva" is utilised to assess the arrival rate, service rate, utilisation rate, line time, and the chance of potential customers baulking. To analyse the given data, Little's Theorem and the M/M/1 queuing model are employed. During our study period, the arrival rate at "Minerva Restaurant" was 3.244 customers per minute (cpm) during its busiest part of the day, while the service rate was 3.28 cpm. The restaurant has an average of 104 customers and a usage period of 0.989 minutes.